A case report of congenitally abnormal rabbitheaded stillbirth Najdi lamb - Mohamed M.M. Elsokary; Seham, F. Shehata; Islam M. Saadedin (The Korean Society of Animal Reproduction and Biotechnology, 2020)
The congenital head anomalies are most often used to describe defects in the eyes, mouth, nose, skull, and or brain. The faulty embryogenesis most likely found to be associated with abnormal genetic or epigenetic causes during pregnancy. Eventually it leads to congenital anomalies. Rabbit-headed Lamb (RH) is a disorder in sheep breeding that is characterized by some deformities in the head and the face. A dead -day old- crossbred white Najdi lamb with a deformed face and head was reported to be born in the current case. The external and physical examination revealed a deformed skull and facial region with a unilateral eye, fused mouth, piglike nose, and patent skull with the brain coming out from left eye orbit. Additionally, the lamb was very skinny with unusual long extremities. This is the first report of this syndrome that describes such deformities in a stillbirth Najdi breed lamb.